When horses pulled boats : a story of early canals - Harlow, Alvin F. (Alvin Fay), 1875-1963; Shank, William H.; Lowell, Orson; Hoffmann, Philip J. (York, PA : American Canal and Transportation Center, 1983)
Surveys the history of canals in America, from colonial times to the twentieth century.
Reprint. Originally published: 1936.
Bibliography: p. 69-70.
Keywords: Canals -- History -- Juvenile literature -- United States; Canals -- History -- United States